2014
DOI: 10.1128/jvi.03359-13
|View full text |Cite
|
Sign up to set email alerts
|

CBFβ Enhances De Novo Protein Biosynthesis of Its Binding Partners HIV-1 Vif and RUNX1 and Potentiates the Vif-Induced Degradation of APOBEC3G

Abstract: Vif is a lentiviral accessory protein that regulates viral infectivity in part by inducing proteasomal degradation of APOBEC3G (A3G). Recently, CBF␤ was found to facilitate Vif-dependent degradation of A3G. However, the exact role of CBF␤ remains unclear. Several studies noted reduced Vif expression in CBF␤ knockdown cells while others saw no significant impact of CBF␤ on Vif stability. Here, we confirmed that CBF␤ increases Vif steady-state levels. CBF␤ affected expression of neither viral Gag nor Vpu protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
1
24
0
1
Order By: Relevance
“…A previous study proposed that CBF-␤ promotes steady-state levels of HIV-1 Vif through the effect on HIV-1 Vif metabolism and biosynthesis (38). As mentioned above, we noticed that the steady-state level of HIV-1 Vif was sensitive to CBF-␤ depletion (Fig.…”
Section: Cbf-␤-kd 293t Cell Generationsupporting
confidence: 54%
See 1 more Smart Citation
“…A previous study proposed that CBF-␤ promotes steady-state levels of HIV-1 Vif through the effect on HIV-1 Vif metabolism and biosynthesis (38). As mentioned above, we noticed that the steady-state level of HIV-1 Vif was sensitive to CBF-␤ depletion (Fig.…”
Section: Cbf-␤-kd 293t Cell Generationsupporting
confidence: 54%
“…Recent studies have shown that the transcription cofactor core-binding factor subunit beta (CBF-␤) is a key factor in Vif function (29,30). CBF-␤ interacts with HIV-1 Vif to enhance Vif's biosynthesis and facilitate Vif folding and stability, thereby enhancing the nucleation of the E3 ubiquitin ligase complex, promoting A3G degradation, and supporting viral infectivity (31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…The recruitment of CBFβ to the Vif E3 ligase is surprising given that CBFβ is a transcription cofactor and not a component of a known cellular E3 ligase. Recruitment of CBFβ serves to stabilize HIV-1 Vif and is required for HIV-1 Vif-mediated A3 degradation activity in vivo (Figure 1) (50, 51, 5355). More recent work has shown that CBFβ is required only for primate lentiviral infection, as it is dispensable for nonprimate Vif function (53, 56).…”
Section: Vifmentioning
confidence: 99%
“…CBFβ normally forms a heterodimer with RUNX family of transcription factors, serving to both stabilize RUNX steady-state levels and to enhance DNA-binding affinity (Huang et al, 2001; Tahirov et al, 2001). Recruitment of CBFβ serves to stabilize HIV-1 Vif and is required for HIV-1 Vif A3 degradation activity in vivo (Hultquist et al, 2012; Jäger et al, 2012b; Kim et al, 2013; Miyagi et al, 2014; Zhang et al, 2012). Recent work has shown that this recruitment alters endogenous RUNX activity through competitive binding of HIV-1 Vif to CBFβ, potentially to the benefit of the virus (Kim et al, 2013; Klase et al, 2014).…”
Section: Introductionmentioning
confidence: 99%